Peningkatan Pemahaman dan Implementasi Customer Relationship Management (CRM) di Industri UMKM Kebumen - Galih Mahardika Munandar; Muhammad Nur Wahyu Hidayah; Alifta Dicasani; Wilson Candra Teguh Pratama; Krisna Adhi Pamungkas; Yusuf Khamid Meilano (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2024)
Public service is a real contribution to strengthening the local economic foundation, the conventional industry sector. "Besides, it's still unclear how consumer behaviour varies. CRM can minimize abstract behaviour based on the data obtained. CRMs can provide consumer behaviour information based on data obtained such as purchasing behaviour. Such data can be enabled in UMKM bank data and build decisions such as discounts, product innovations and product sales. Increasing CRM in the context of society is crucial to strengthening the bond between the convenience industry and its consumers. The proposed community enhancement involves a series of holistic activities that are not aimed at improving employee understanding and integrating such methods into everyday practice